2019
DOI: 10.3390/app9183736
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cavitation Noise in Cavitating Flows around an NACA0015 Hydrofoil

Abstract: To provide theoretical basis for cavitation noise control, the cavitation evolution around a hydrofoil and its induced noise were numerically investigated. A modified turbulence model and Zwart cavitation model were employed to calculate the flow field and predict the cavitation phenomenon accurately. Then, the acoustic analogy method based on the Ffowcs Williams-Hawking (FW-H) equation was applied to analyze the cavitation-induced noise. Seven cavitation numbers were selected for analysis. Acoustic power spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The previous investigations revealed the characteristics of natural cavitation induced noise around a NACA0015 hydrofoil (Yu et al 2019). It is confirmed that with the decreasing of cavitation number, the magnitude of acoustic power spectral density (PSD) increased significantly, which can be attributed to their difference in cavitation evolution.…”
Section: Noise Pattern Of Nature Cavitationmentioning
confidence: 60%
“…The previous investigations revealed the characteristics of natural cavitation induced noise around a NACA0015 hydrofoil (Yu et al 2019). It is confirmed that with the decreasing of cavitation number, the magnitude of acoustic power spectral density (PSD) increased significantly, which can be attributed to their difference in cavitation evolution.…”
Section: Noise Pattern Of Nature Cavitationmentioning
confidence: 60%
“…Additionally, several studies have demonstrated that combining CFD and acoustic analogies based on the Williams and Hawkings (FW-H) equation is effective [19] . To investigate unsteady cavitation around a NACA0015 hydrofoil and its associated noise, Yu et al [20] combined a filter-based turbulence model with the Zwart-Gerbera-Belamri (ZGB) cavitation model. To predict hydrodynamic noise, caused by tip-vortex cavitation (TVC) of submarine propellers, Ku et al [21] employed delayed detached eddy simulation (DDES) with adaptive mesh refinement and the FW-H equation, and concluded that a higher pitch angle resulted in more noise.…”
Section: Introductionmentioning
confidence: 99%
“…However, scholars mainly considered the accuracy of numerical calculation methods and the mechanism of TLV cavitation, while ignoring the interaction between tip clearance specifications and TLV cavitation and noise. In order to ensure the accuracy of noise prediction, scholars have taken into account the impact of turbulence models on prediction and analysis noise [7]. The research shows that the turbulence model harms the noise sources of single-stage and induced effects.…”
Section: Introductionmentioning
confidence: 99%